Assessment of compost quality in agitated pile composting of water hyacinth collected from different sources - Jiwan Singh; Ajay S. Kalamdhad (International Journal of Recycling of Organic Waste in Agriculture)
Background Water hyacinth (Eichhornia crassipes) can cause a diversity of problems due to its fast spread and congested growth. The composting of water hyacinth can reduce the chemical fertilizer application to the agricultural field and problems related to its fast growth rate and also help in nutrient recycling. The present study was carried out on agitated pile composting of water hyacinth collected from four different areas (Bharalu River, Agriculture site, Boragaon landfill site and Industrial site). The nutrients and stability parameters were evaluated during the 30 days of agitated pile composting of water hyacinth mixed with cattle manure and sawdust. The stability of compost was evaluated using respiration techniques (CO2 evolution and oxygen uptake rate). Results Results showed that nutrients (Na, K, Ca, total nitrogen and phosphorus) were increased significantly in all agitated pile composting. Stability parameters such as CO2 evolution rate and oxygen uptake rate, biochemical chemical oxygen demand and chemical oxygen demand were reduced significantly during the process. Highest reduction of moisture content (35.2 %), volatile solid (40.5 %), ammonical nitrogen (75.6 %), biochemical oxygen demand (65.3 %), CO2 evolution rate (78.7 %), and oxygen uptake rate (74.4 %) were observed in the agitated pile of Bharalu River site as compared to other agitated piles. The higher increase of total nitrogen (83.5 %) and total phosphorus (76.0 %) was also observed in the agitated pile of Bharalu River site. Conclusion Addition of optimum amount of cattle manure was highly efficient for making compost of water hyacinth collected from four different sites. Highest content of nutrients was found in compost of water hyacinth collected from Bharalu River site due to availability of nutrients in sewage water. In the final compost of all trials, total coliform and fecal coliform were reduced significantly, which are pathogen indicators in the compost. The best compost quality was found in water hyacinth collected from Bharalu River site.